Factors affecting the market value of football players in the Indonesian League - Al Hazmi, Raldin Alif (PT Wim Solusi Prima, 2024)
The development of accounting science, especially in human resource accounting (HRA), has progressed rapidly. The understanding of human resources (HR) as a vital asset that has an important role in the success of an organization is growing. This research focuses on measuring the market value of professional football players in the Indonesian League by considering individual performance, especially for players who play as central midfielders. Football players, recognized as intangible assets, have a market value that is closely related to their contribution on the field. The research method used is quantitative with a descriptive approach, examining the relationship between performance variables (goals, assists, number of appearances, yellow cards, and red cards) to player market value. The research data was obtained through secondary data sources from the transfermarkt.co.id website with a sample of 52 Indonesian central midfield players in the 2023 season. The results showed that goals, assists, and number of appearances had a significant influence on the player's market value. Assists and number of appearances show a very strong influence on player prices, while yellow cards and red cards do not show a significant influence. This research provides important insights for football club management in determining the market value of players as part of financial reporting and investment decision-making, and enriches the study of human resource accounting in the football industry. The findings also show the importance of players' positive on-field contributions, such as assists and performances, in determining their market value, beyond disciplinary factors such as yellow and red cards.